Player tracking in soccer: Is a newly developed GPS tracking device fit for pursose? - Healey, M. S.; Lightfoot, C.; Clarke, N. (Sport Performance & Science Reports, 2021)
Global Positioning System (GPS) technology has been increasingly used for a number of years to monitor player performance during training and match-play . Furthermore, during the COVID-19 pandemic, match-play and training in soccer changed , with restrictions including remote training and reduced numbers. These changes resulted in players having to train away from their usual support network, coaches and support staff unable to collect data and monitor players as before and raised the question of what alternatives there are and the cost benefit to use. Aim To evaluate a recently developed GPS technology as a method of collecting player physical data and compare this with an existing, established GPS technology already being employed in football.